The Uruguay Round and the Arab Countries. (International Monetary Fund, 1996)
The benefits and challenges of the liberalization measures encompassed under the Uruguay Round were the subject of aseminar sponsored by the IMF, the Arab Fund for Economic and Social Development, the Arab Monetary Fund, and the World Bank. The papers presented in this publication, edited by Said El-Naggar, review the results of the Uruguay Round, examine the broad policy and macroeconomic implications of trade reform for the Arab countries, and consider certain of the sectoral trade reform measures - including trade in agricultural product, textiles and clothing, and services- embodied in the Uruguay Round agreement and their impact on the Arab countries.